Design and Experiment of Electric Uncrewed Transport Vehicle for Solanaceous Vegetables in Greenhouse - Chunsong Guan; Weisong Zhao; Binxing Xu; Zhichao Cui; Yating Yang; Yan Gong (Agriculture)
Despite some rudimentary handling vehicles employed in the labor-intensive harvesting and transportation of greenhouse vegetables, research on intelligent uncrewed transport vehicles remains limited. Herein, an uncrewed transport vehicle was designed for greenhouse solanaceous vegetable harvesting. Its overall structure and path planning were tailored to the greenhouse environment, with specially designed components, including the electric crawler chassis, unloading mechanism, and control system. A SLAM system based on fusion of LiDAR and inertial navigation ensures precise positioning and navigation with the help of an overall path planner using an A* algorithm and a 3D scanning constructed local virtual environment. Multi-sensor fusion localization, path planning, and control enable autonomous operation. Experimental studies demonstrated it can automatically move, pause, steer, and unload along predefined trajectories. The driving capacity and range of electric chassis reach the design specifications, whose walking speeds approach set speeds (<5% error). Under various loads, the vehicle closely follows the target path with very small tracking errors. Initial test points showed high localization accuracy at maximum longitudinal and lateral deviations of 9.5 cm and 6.7 cm, while the average value of the lateral deviation of other points below 5 cm. These findings contribute to the advancement of uncrewed transportation technology and equipment in greenhouse applications.